Introduction to biomechatronics - Brooker, Graham (SciTech Pub., 2012)
Biomechatronics is the application of mechatronic engineering to human biology, and, as such, it forms an important subset of the overall biomedical engineering discipline. As with mechatronics, which is often synonymous with robotics, biomechatronics is often thought of as restricted to the development of prosthetic limbs. However, in reality biomechatronics covers a much wider genre than this, and along with prosthetic limbs this book examines some of the more interesting applications including those related to hearing, respiration, vision, and the cardiovascular system.
Keywords: Biomedical engineering.; Medical instruments and apparatus.; Robotics.; Mechatronics.; elektronické knihy; electronic books